Process-Oriented Guided Inquiry Learning and Students' Mathematical Reasoning Ability in Indonesia: A Systematic Literature Review and Meta-Analysis - Nurtamam, Mohammad Edy; Budayasa, I Ketut; Lukito, Agung (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study analyzes the effectiveness of the Process-Oriented Guided Inquiry Learning (POGIL) model in enhancing the mathematical reasoning ability of students in Indonesia. A systematic literature review and meta-analysis approach was employed. The inclusion criteria required data to be sourced from international journals and proceedings indexed in the Science and Technology Index (SINTA), Scopus, and Web of Science. Research data were collected from databases such as Google Scholar, ScienceDirect, Mendeley, Wiley, Springer, and ERIC. Studies included in the analysis were published between 2020 and 2024, focused on the POGIL model and students' mathematical reasoning ability, and provided complete data for effect size calculation. Keywords used for data searches included